Unlocking the Potential: Exploring the Influence of Artificial Intelligence on E-Health Enhancement in South Africa - Lehlohonolo Josiaya Malope (Journal of Economic and Social Development (Varaždin))
The study titled "Unlocking the Potential: Examining the Impact of Artificial Intelligence on Improving EHealth in South Africa" examines how artificial intelligence (AI) can help solve the substantial inequalities in healthcare access and quality in South Africa. Despite persistent actions to enhance healthcare services, a significant disparity persists, especially in remote and disadvantaged areas. This study seeks to investigate the ways in which AI can improve e-health services, with a specific focus on its ability to address the healthcare gap and enhance results throughout the entire country. The study utilizes a qualitative approach, examining pre-existing literature, policy papers, and expert viewpoints to clarify the influence of AI on the provision of healthcare. The results emphasize that AI technologies, such as Virtual Health Assistants (VHAs) and remote monitoring systems, can greatly reduce the workload on public healthcare institutions, improve the management of chronic diseases, and automate administrative duties. Through the optimization of these processes, artificial intelligence (AI) has the potential to allocate more time for healthcare workers to prioritize patient care. Furthermore, the article highlights the need of tackling obstacles such as concerns around the protection of data and the requirement for strong digital infrastructure to facilitate the deployment of AI. Suggested measures involve allocating resources towards customized artificial intelligence solutions, improving the training of healthcare professionals, and promoting cooperation among relevant parties to develop efficient electronic health initiatives. In conclusion, the article highlights the capacity of AI to transform healthcare in South Africa, by ensuring fair availability of high-quality treatments and enhancing health results for the entire population. Through addressing current barriers and harnessing the potential of artificial intelligence, South Africa has the potential to make substantial progress in attaining universal healthcare coverage and guaranteeing universal access to vital healthcare services.